Poly(hydroxyurethane‐co‐thiourethane)s cross‐linked with disulfide bonds: Synthesis via isocyanate‐free approach, thermomechanical and reprocessing properties. Issue 19 (15th June 2022) - Liu, Weiming; Ge, Wenming; Mei, Honggang; Hang, Guohua; Li, Lei; Zheng, Sixun
Abstract: Both difunctional five‐membered cyclic carbonate (E5CC) and trithiocarbonate (E5CTC) were synthesized via the reactions of diglycidyl ether of bisphenol A (DGEBA) with carbon dioxide (CO2 ) and carbon disulfide (CS2 ), respectively. These two monomers were employed to synthesize linear poly(hydroxyurethane‐ co ‐mecaptotrithiourethane) [P(HU‐ co ‐MTU)] copolymers via the polymerization with an α, ω‐diamino‐terminated poly(propylene oxide). By controlling the mole ratios of E5CC to E5CTC, the P(HU‐ co ‐MTU) copolymers were synthesized with variable contents of thiol groups. It was found that the linear P(HU‐ co ‐MTU) copolymers were readily cross‐linked with the disulfide bonds which were in situ generated via the radical coupling of the side thiol groups. The cross‐linking exerted a profound impact on the thermomechanical properties of the materials. The glass transition temperature ( T g 's), Young's moduli and tensile strengths were significantly enhanced with increasing the contents of disulfide bonds. More importantly, the networks significantly displayed the self‐healing and reprocessing properties, which are attributable to the dynamic exchanges of disulfide bonds. Abstract :